Catastrophic failure of the back facet in watt-level power long wavelength infrared quantum cascade laser. (8th September 2022) - Yin, Ran; Zhang, Jin-Chuan; Guo, Qiang-Qiang; Zhuo, Ning; Zhai, Shen-Qiang; Jia, Zhi-wei; Liu, Jun-Qi; Wang, Li-Jun; Liu, Shu-Man; Lu, Quan-Yong; Liu, Feng-Qi; Wang, Zhan-Guo
Abstract: Quantum cascade lasers (QCLs) suffer from catastrophic failure caused by serious self-heating, thus limiting their output power and working stability. In this study, we observed a distinctive failure morphology on the back facet of watt-level power QCL emitting at λ ∼ 7.7 µ m. The failure was caused by a massive localized current and the channel of the massive current can be observed in the cavity. Because the massive current significantly increased temperature nearby, two burned holes were formed around the channel. A 3D thermal model shows that the back facet is a vulnerable location for failure because light absorption by the high-reflectance metal coating increases the facet temperature significantly. However, the starting point of the massive current has a certain distance from the facet which is the hottest location in the cavity. Therefore, we conduct a hypothesis that the cause of the massive current is thermal strain relaxations induced by temperature gradient. We calculated the positions of the relaxation points and one of them correspond with the failure starting point found experimentally. The strain relaxation damaged the active region, thus leading to the formation of the massive current.